2001
DOI: 10.1177/000765030104000103
|View full text |Cite
|
Sign up to set email alerts
|

Culture, Perceived Corruption, and Economics

Abstract: Corruption can impede commerce and economic development, yet it seems to be tolerated in many countries. The purpose of this study was to develop and test a model that integrates socioeconomic factors related to corruption. The analysis revealed that a negative relationship between economic adversity and wealth was mediated by corruption. Economic adversity was positively related to corruption, and corruption was inversely related to wealth. Uncertainty avoidance moderated the relationship between economic adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
194
0
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(229 citation statements)
references
References 33 publications
(49 reference statements)
12
194
0
12
Order By: Relevance
“…While there is a paucity of crosscultural research that has investigated the impact of macro-level factors (e.g., economic development) on micro-level behaviors (e.g., influence), macrolevel research has shown that economic development level is related to ethical business conduct. Specifically, the prevalence of unethical and corrupt business practices has been found to be negatively related to economic development level (Collins, 2000;Davis & Ruhe, 2003;Getz & Volkema, 2001;Husted, 1999;Mauro, 1995;Treisman, 2007). One explanation can be found in institutional anomie theory, which identifies the ends vs means issue faced by individuals in developing or have-not societies (Merton, 1968).…”
Section: A Business Ideology Model Of Subordinate Influence Ethicsmentioning
confidence: 99%
See 2 more Smart Citations
“…While there is a paucity of crosscultural research that has investigated the impact of macro-level factors (e.g., economic development) on micro-level behaviors (e.g., influence), macrolevel research has shown that economic development level is related to ethical business conduct. Specifically, the prevalence of unethical and corrupt business practices has been found to be negatively related to economic development level (Collins, 2000;Davis & Ruhe, 2003;Getz & Volkema, 2001;Husted, 1999;Mauro, 1995;Treisman, 2007). One explanation can be found in institutional anomie theory, which identifies the ends vs means issue faced by individuals in developing or have-not societies (Merton, 1968).…”
Section: A Business Ideology Model Of Subordinate Influence Ethicsmentioning
confidence: 99%
“…We made this decision for the following reasons. First, the individualism and collectivism dimensions have been used consistently in previous cross-cultural research on ethical decision-making and business corruption (Cherry, Lee, & Chien, 2003;Davis & Ruhe, 2003;Getz & Volkema, 2001;Thorne & Saunders, 2002;Volkema, 2004). Second, there is substantial consensus that individualism is the most pervasive and reliable sociocultural dimension (Oyserman, Coon, & Kemmelmeier, 2002).…”
Section: A Sociocultural Model Of Subordinate Influence Ethicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, which examined the relationship between corruption and economic factors, Getz and Volkema (2001) found that economic uncertainties increased the general level of prices, and the increase in inflation triggered corruption. The study by Paldam (2002), which investigated the economic and cultural determinants of corruption, revealed that an increase in inflation rates gave rise to corruption in the short term.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, accountants guided by economic rationality are likely to use their colleagues to develop a favorable assessment of a client firm from which they can gain a financial advantage. Although prior research has not examined the impact of economic rationalization on accountants' values, few studies have found a lower concern with ethical behavior in countries with a higher level of economic rationalization (Franke and Nadler 2008;Getz and Volkema 2001).…”
Section: Impact Of Economic Rationalization On Self-transcendence Valuesmentioning
confidence: 99%